2020
DOI: 10.1016/j.ophtha.2019.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Associations with Different Macular Inner Retinal Thickness Parameters in a Large Cohort

Abstract: Purpose: To describe and compare associations with macular retinal nerve fiber layer (mRNFL), ganglion cell complex (GCC), and ganglion celleinner plexiform layer (GCIPL) thicknesses in a large cohort.Design: Cross-sectional study.Participants: We included 42 044 participants in the UK Biobank. The mean age was 56 years. Methods: Spectral-domain OCT macular images were segmented and analyzed. Corneal-compensated intraocular pressure (IOPcc) was measured with the Ocular Response Analyzer (Reichert, Corp., Buffa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
95
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 37 publications
8
95
4
Order By: Relevance
“…The present study found that greater alcohol consumption was significantly associated with thinner macular GCIPL thickness after compensation for several confounding factors including baseline IOP, AXL, and optic nerve head parameters. This is consistent with a recent large UK cohort study reporting that frequent alcohol consumption is associated with thinner macular RNFL, GCC and GCIPL 16 . Speculative explanations for the present finding are as follows.…”
Section: Discussionsupporting
confidence: 93%
“…The present study found that greater alcohol consumption was significantly associated with thinner macular GCIPL thickness after compensation for several confounding factors including baseline IOP, AXL, and optic nerve head parameters. This is consistent with a recent large UK cohort study reporting that frequent alcohol consumption is associated with thinner macular RNFL, GCC and GCIPL 16 . Speculative explanations for the present finding are as follows.…”
Section: Discussionsupporting
confidence: 93%
“…24 These included poor SD OCT signal strength, 24 image quality score < 45, poor centration certainty, or poor segmentation certainty, when examining the association of ambient air pollution on GCIPL. 25…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…8 Inner retinal measures were also significantly lower in participants with greater alcohol intake, more social deprivation and lower educational attainment. 8 The strongest association observed was between mGCIPL thinning and IOP elevation, highlighting the relevance of excluding glaucoma. With reference to the study by Filippatou et al, 3 it should be noted that ocular hypertension and primary open angle glaucoma are conditions five times more likely to affect African Americans than Caucasians, 9 which may have impacted their results since African Americans made up a third of their obese cohort.…”
mentioning
confidence: 91%
“…Other factors related to lower mRNFL, mGCC and mGCIPL measures were age, male gender and non-Caucasian Editorial ethnicity. 8 The thinner mGCC thickness seen in Blacks compared with Whites in the UK Biobank study had a magnitude of 26% of the standard deviation of this measure, equivalent to being 10 years older. 8 Inner retinal measures were also significantly lower in participants with greater alcohol intake, more social deprivation and lower educational attainment.…”
mentioning
confidence: 97%
See 1 more Smart Citation